Evaluating novel approaches for estimating awake and sleep blood pressure: design of the Better BP Study – a randomised, crossover trial - Paul Muntner; Ligong Chen; Daichi Shimbo; Joseph E Schwartz; Maria Cepeda; Demetria Hubbard; Suzanne Oparil; Byron C Jaeger; Shakia T Hardy; Julia Medina (BMJ Open)
Introduction For many people, blood pressure (BP) levels differ when measured in a medical office versus outside of the office setting. Out-of-office BP has a stronger association with cardiovascular disease (CVD) events compared with BP measured in the office. Many BP guidelines recommend measuring BP outside of the office to confirm the levels obtained in the office. Ambulatory BP monitoring (ABPM) can assess out-of-office BP but is not available in many US practices and some individuals find it uncomfortable. The aims of the Better BP Study are to (1) test if unattended office BP is closer to awake BP on ABPM compared with attended office BP, (2) assess if sleep BP assessed by home BP monitoring (HBPM) agrees with sleep BP from a full night of ABPM and (3) compare the strengths of associations of unattended versus attended office BP, unattended office BP versus awake BP on ABPM and sleep BP on HBPM versus ABPM with markers of end-organ damage.Methods and analysis We are recruiting 630 adults not taking antihypertensive medication in Birmingham, Alabama, and New York, New York. Participants are having their office BP measured with (attended) and without (unattended) a technician present, in random order, using an automated oscillometric office BP device during each of two visits within one week. Following these visits, participants complete 24 hours of ABPM and one night of HBPM, in random order. Psychosocial factors, anthropometrics, left ventricular mass index and albumin-to-creatinine ratio are also being assessed.Ethics and dissemination This study was approved by the University of Alabama at Birmingham and the Columbia University Medical Center Institutional Review Boards. The study results will be disseminated at scientific conferences and published in peer-reviewed journals.Trial registration number NCT04307004.